Rigidity Test Using The Pebble Game Distributed Implementation - BOURAS, Ibrahim; Research Director: Moussaoui, Adel (University of M'sila, 2016)
James Clark Maxwell wondered: counting vertices and edges in a given framework is enough to make predictions about its rigidity and fexibility? Laat in 1970 confirmed that the 24 generic bar and joint frameworks is completely combinatorial problem. Le counting is enough to decide.. The 2V-3 counting condition for 24 structures verified by the last pebble game algorithm which tracks quickly this count. Hendrickson and jacobs proposed the centralized pebble gume version in 1997. In 2014, group of researchers proposed the decentralized version in IEEE In this thesis, we the implement the asynchronous, distributed algorithm of the pebble game for testing the rigidity in 2d framework, using java threads and interprocess communicatons protocols. We have also introduced several rigidity theory applications, we will apply our algorithm on some 2d strucutres. The results obtained in this Master theisis showed that our distributed implementation is well done and worked.
Keywords: Rigidity, Flexibility, Laman graph, pebble gume algorithm.